Revitalizing Minangkabau Traditional Values as a Solution to the Multicultural Education Crisis in West Sumatra - Gucandra, Yudi; Aprison, Wedra (Jurnal Kajian dan Pengembangan Umat, 2025)
This study analyzes the paradox of multicultural education in West Sumatra, where the Minangkabau traditional philosophy, rich in egalitarian and tolerant values, has not been optimally integrated into the formal education system, triggering a crisis marked by religious intolerance, bullying, and ethnic tensions. Using a qualitative approach with hermeneutic methods and content analysis of policy documents, media reports (2024-2025), and academic literature, this study identifies systemic failures in Banks' five dimensions of multicultural education: Prejudice Reduction (religious intolerance), Equity Pedagogy and Empowering School Culture (bullying), and Content Integration and Knowledge Construction (ethnic tension). The findings show that the crisis is not caused by the absence of tolerance values, but rather by the failure to translate traditional philosophy into concrete practice. This study proposes a model for revitalizing Minangkabau traditional values as a contextual solution: (1) ABS-SBK interpreted inclusively to reduce prejudice; (2) deliberative consensus as the basis for equitable pedagogy; (3) the principles of "Duduak Samo Randah, Tagak Samo Tinggi" (sit low, stand tall) and "Dima Bumi Dipijak, Disinan Langik Dijunjuang" (wherever you step, that is where heaven is) to build an egalitarian school culture that respects diversity. The proposed "Contextual Multicultural Education" model synthesizes the universal principles of multicultural education with local wisdom, while adopting a critical approach that does not romanticize traditional values but interprets them transformatively. This research contributes theoretically by enriching the discourse on multicultural education through the perspective of Indigenous Knowledge, empirically by documenting concrete cases in West Sumatra, and practically by offering policy recommendations for the reformulation of local content curricula, teacher training based on local wisdom, and school culture transformation.